MONTESSORI LEARNING IMPACT ON CHILDREN'S ENGLISH SPEAKING SKILLS AT FL HAUS INSTITUTE, SERANG CITY - Apria Gina, Agnes; Tarihoran, Nafan; Rika Perdana, Purnama (Jurnal Ilmiah Bina Bahasa, 2025)
This study examines the impact of Montessori education on children's English-speaking skills at the FL HAUS INSTITUTE, Serang City. Grounded in early childhood language acquisition theory, the research employs a descriptive qualitative approach, collecting data through observations and interviews with young learners and their parents. The findings suggest that Montessori learning promotes language development by creating an interactive and engaging environment, thereby enhancing children's confidence and communication skills. The study highlights the critical role of parents and teachers in supporting early language growth through structured Montessori activities. Additionally, it contributes to the refinement of Montessori curricula by emphasizing the integration of well-designed oral communication exercises. The research highlights the effectiveness of a child-centered learning approach in enhancing English proficiency, underscoring the importance of Montessori education in early childhood development and its broader implications for language learning methodologies.